An Aptitude for Altitude: Are Epigenomic Processes Involved? - Julian, Colleen G. (Frontiers in Physiology, 2019)
In recent years, high-throughput genomic technologies and computational advancements have invigorated efforts to identify the molecular mechanisms regulating human adaptation to high altitude. Although exceptional progress regarding the identification of genomic regions showing evidence of recent positive selection has been made, many of the key “hypoxia tolerant” phenotypes of highland populations have not yet been linked to putative adaptive genetic variants. As a result, fundamental questions regarding the biological processes by which such adaptations are acquired remain unanswered. This Mini Review discusses the hypothesis that the epigenome works in coordination with underlying genomic sequence to govern adaptation to the chronic hypoxia of high altitude by influencing adaptive capacity and phenotypic variation under conditions of environmental hypoxia. Efforts to unravel the complex interactions between the genome, epigenome, and environmental exposures are essential to more fully appreciate the mechanisms underlying human adaptation to hypoxia.